Artemether‐lumefantrine co‐administration with antiretrovirals: population pharmacokinetics and dosing implications. (April 2015) - Hoglund, Richard M.; Byakika‐Kibwika, Pauline; Lamorde, Mohammed; Merry, Concepta; Ashton, Michael; Hanpithakpong, Warunee; Day, Nicholas P. J.; White, Nicholas J.; Äbelö, Angela; Tarning, Joel
Abstract : Aim: Drug–drug interactions between antimalarial and antiretroviral drugs may influence antimalarial treatment outcomes. The aim of this study was to investigate the potential drug–drug interactions between the antimalarial drugs, lumefantrine, artemether and their respective metabolites desbutyl‐lumefantrine and dihydroartemisinin, and the HIV drugs efavirenz, nevirapine and lopinavir/ritonavir. Method: Data from two clinical studies, investigating the influence of the HIV drugs efavirenz, nevirapine and lopinavir/ritonavir on the pharmacokinetics of the antimalarial drugs lumefantrine, artemether and their respective metabolites, in HIV infected patients were pooled and analyzed using a non‐linear mixed effects modelling approach. Results: Efavirenz and nevirapine significantly decreased the terminal exposure to lumefantrine (decrease of 69.9% and 25.2%, respectively) while lopinavir/ritonavir substantially increased the exposure (increase of 439%). All antiretroviral drugs decreased the total exposure to dihydroartemisinin (decrease of 71.7%, 41.3% and 59.7% for efavirenz, nevirapine and ritonavir/lopinavir, respectively). Simulations suggest that a substantially increased artemether‐lumefantrine dose is required to achieve equivalent exposures when co‐administered with efavirenz (250% increase) and nevirapine (75% increase). When co‐administered with lopinavir/ritonavir it is unclear if the increased lumefantrine exposure compensates adequately for the reduced dihydroartemisinin exposure and thus whether dose adjustment is required. Conclusion: There are substantial drug interactions between artemether‐lumefantrine and efavirenz, nevirapine and ritonavir/lopinavir. Given the readily saturable absorption of lumefantrine, the dose adjustments predicted to be necessary will need to be evaluated prospectively in malaria‐HIV co‐infected patients.